UJI EFEKTIVITAS SEDIAAN KRIM EKSTRAK ETANOL DAUN MIANA (Coleus scutellarioides L.)TERHADAP BAKTERI Propionibacterium acnes - Gusti Alam; Maulana, Maulana Zulkarnain Imansyah; Sarifuddin Side (Jurnal Kesehatan Yamasi Makassar, 2023)
Miana leaves (Coleus Scutellarioides L.) is one of the plants that are often used as an ornamental plant and herbal medicine, this plant is widely distributed in the Asian region. Miana leaves are often used as traditional medicines for responders such as angina, antioxidants, antibacterials and ulcers. Miana leaves have ingredients such as essential oils, carvacol, flavonoids, tannins, ethyl salicylates and oxalic acid. This study aims to determine the antibacterial activity of miana leaf ethanol extract cream (Coleus Scutellarioides L.) against propionibacterium acnes bacteria. This research was conducted using the laboratory experimental research method. In the preparation of cream extract ethanol miana leaves (Coleus scutellarioides L.) with a concentration of 15%, 10%, 5%, respectively. Testing was carried out on propionibacterium acnes bacteria using the paper disk diffusion method. Based on the results of research, miana leaf ethanol extract cream (Coleus Scutellarioides L) is less able to inhibit the growth of propionibacterium acnes bacteria.